IKZF1plus defines a new minimal residual disease-dependent very-poor prognostic profile in pediatric B-cell precursor acute lymphoblastic leukemia - Stanulla, Martin; Dagdan, Elif; Zaliova, Marketa; Möricke, Anja; Palmi, Chiara; Cazzaniga, Giovanni; Eckert, Cornelia; te Kronnie, Geertruy; Bourquin, Jean-Pierre; Bornhauser, Beat; Köhler, Rolf; Bartram, Claus R.; et al. (Journal of clinical oncology, 2018)
Purpose: Somatic deletions that affect the lymphoid transcription factor-coding gene IKZF1 have previously been reported as independently associated with a poor prognosis in pediatric B-cell precursor (BCP) acute lymphoblastic leukemia (ALL). We have now refined the prognostic strength of IKZF1 deletions by analyzing the effect of co-occurring deletions.Patients and MethodsThe analysis involved 991 patients with BCP ALL treated in the Associazione Italiana Ematologia ed Oncologia Pediatrica-Berlin-Frankfurt-Muenster (AIEOP-BFM) ALL 2000 trial with complete information for copy number alterations of IKZF1, PAX5, ETV6, RB1, BTG1, EBF1, CDKN2A, CDKN2B, Xp22.33/Yp11.31 (PAR1 region; CRLF2, CSF2RA, and IL3RA), and ERG; replication of findings involved 417 patients from the same trial.ResultsIKZF1 deletions that co-occurred with deletions in CDKN2A, CDKN2B, PAX5, or PAR1 in the absence of ERG deletion conferred the worst outcome and, consequently, were grouped as IKZF1plus. The IKZF1plus group comprised 6% of patients with BCP ALL, with a 5-year event-free survival of 53 ± 6% compared with 79 ± 5% in patients with IKZF1 deletion who did not fulfill the IKZF1plus definition and 87 ± 1% in patients who lacked an IKZF1 deletion (P ≤ .001). Respective 5-year cumulative relapse incidence rates were 44 ± 6%, 11 ± 4%, and 10 ± 1% (P ≤ .001). Results were confirmed in the replication cohort, and multivariable analyses demonstrated independence of IKZF1plus. The IKZF1plus prognostic effect differed dramatically in analyses stratified by minimal residual disease (MRD) levels after induction treatment: 5-year event-free survival for MRD standard-risk IKZF1plus patients was 94 ± 5% versus 40 ± 10% in MRD intermediate- and 30 ± 14% in high-risk IKZF1plus patients (P ≤ .001). Corresponding 5-year cumulative incidence of relapse rates were 6 ± 6%, 60 ± 10%, and 60 ± 17% (P ≤ .001).ConclusionIKZF1plus describes a new MRD-dependent very-poor prognostic profile in BCP ALL. Because current AIEOP-BFM treatment is largely ineffective for MRD-positive IKZF1plus patients, new experimental treatment approaches will be evaluated in our upcoming trial AIEOP-BFM ALL 2017.